Estimating the Probabaility of Mining-Induced Seismic Events using Mine-Scale, Inelastic Numerical Models - Beck, D.; Reusch, F.; Arndt, S. (Deep Mining 2007: Proceedings of the Fourth International Seminar on Deep and High Stress Mining, 2007)
Detailed, mine-scale non-linear numerical models have been calibrated using observations of displacement and damage at three deep mines. The calibrated models were then used to investigate the correlation between Dissipated Plastic Energy (DPE) and seismic event probability. A strong, non-linear relation between DPE and event probability was observed that describes the development, peak, and decline in seismicity as rock is deformed. The correlations are present for events at all magnitudes, and the where sufficient data was available for a comparison, a relation between DPE and event probability consistent with the relation between event magnitude and frequency described by the Gutenberg Richter equation was found. The application of DPE analysis during the design and sequencing of mines will allow a more quantitative description of seismic hazards than is currently available.